Conventional aortic valve replacement can be safely done by very early stage trainee - Shirakura, Kentaro; Mochizuki, Nobuhiro; Ushioda, Ryohei; Kunioka, Shingo; Tsutsui, Masahiro; Kamiya, Hiroyuki (Frontiers in Surgery, 2025)
ObjectivesWe have continuously performed conventional aortic valve replacement (AVR) with median sternotomy as the primary approach because we believe that it is the safest approach, and even very young trainees have performed surgical AVR (SAVR) under proper supervision. Here we reviewed our results of AVR to clarify whether our aggressive training program would be justified.MethodsThis retrospective study evaluates the outcomes of trainee surgeons performing SAVR under supervision at a single institution. We analyzed 145 patients who underwent isolated SAVR between January 2015 and April 2024. Patients were divided into two groups: those operated on by staff surgeons with more than 7 years of postgraduate experience in the Japanese residency program (n = 91), and those operated on by resident surgeons with 2–6 years of postgraduate experience in the Japanese residency program (n = 54). Outcomes compared preoperative characteristics, intraoperative metrics, postoperative complications, and survival rates.ResultsResults showed no significant difference in operative time, and aortic cross-clamp time between the groups. Furthermore, early postoperative mortality and mid-term survival rates were comparable. Although staff surgeons had higher Japan SCORE, residents demonstrated similar clinical outcomes.ConclusionsSAVR can be safely performed by very early-stage trainees under proper case selection and supervision.